Pilot study of the occurrence of somatic mutations in ciliary signalling pathways as a contribution factor to autosomal dominant polycystic kidney development - Hlinková, Katarína; Hrčková, Gabriela; Vaská, Anita; Baranyaiová, Agnes; Janega, Pavol; Žilinská, Zuzana; Daniš, Dušan; Kovács, László (Folia biologica (Praha), 2017)
Autosomal-dominant polycystic kidney disease (ADPKD) is an inherited disease that results in multiple kidney cysts, and it is a common cause of end-stage renal disease. Recent studies have shown that disease progression can be slowed by simultaneous disruption of the primary cilium and polycystins. The exact genetic mechanism of this process is still unknown. The aim of the present study was to characterize the mutation profile of ciliary signalling pathways in the renal epithelial cells of ADPKD patients. In our study, we performed an analysis of 110 genes encoding the components of Sonic Hedgehog, Hippo, Notch, Wnt and planar cell polarity signalling (PCP) by targeted next-generation sequencing. We analysed 10 formalin-fixed, paraffinembedded (FFPE) tissue samples of patients with ADPKD. We identified a unique mutation profile in each of the analysed ADPKD samples, which was characterized by the presence of pathogenic variants in eight to 11 genes involved in different signalling pathways. Despite the significant genetic heterogeneity of ADPKD, we detected five genes whose genetic variants affected most ADPKD samples. The pathogenic variants in NCOR2 and LRP2 genes were present in all analysed samples of ADPKD. In addition, eight out of 10 samples showed a pathogenic variant in the MAML2 and FAT4 genes, and six out of 10 samples in the CELSR1 gene. In our study, we identified the signalling molecules that may contribute to the cystogenesis and may represent potential targets for the development of new ADPKD treatments.
Keywords: mutace; DNA vazebné proteiny; dospělí; kationtové kanály TRPP; Nuclear Proteins; Polycystic Kidney Diseases; Polycystic Kidney, Autosomal Dominant; jaderné proteiny; korepresor 2 jaderného receptoru; transkripční faktory; Adult; nádorové supresorové proteiny; Nuclear Receptor Co-Repressor 2; Low Density Lipoprotein Receptor-Related Protein-2; lidé; Pilot Projects; Transcription Factors; signální transdukce; pilotní projekty; Mutation; Signal Transduction; polycystické ledviny autozomálně dominantní; protein 2 související s LDL-receptory; polarita buněk; progrese nemoci; Tumor Suppressor Proteins; TRPP Cation Channels; Disease Progression; DNA-Binding Proteins; Cell Polarity; Cadherins; lidé středního věku; polycystická choroba ledvin; kadheriny; Middle Aged; Humans